Serum hyaluronic acid as a predictor of fibrosis in chronic hepatitis B and C virus infection. - Nath, NC; Rahman, MA; Khan, MR; Hasan, MS; Bhuiyan, TM; Hoque, MN; Kabir, MM; Raha, AK; Jahan, B (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):614-9 The abstract of this article is available on the PubMed website